2021
DOI: 10.1016/j.molmet.2021.101300
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte CAMK2 deficiency improves obesity-associated glucose intolerance

Abstract: Objective Obesity-related adipose tissue dysfunction has been linked to the development of insulin resistance, type 2 diabetes, and cardiovascular disease. Impaired calcium homeostasis is associated with altered adipose tissue metabolism; however, the molecular mechanisms that link disrupted calcium signaling to metabolic regulation are largely unknown. Here, we investigated the contribution of a calcium-sensing enzyme, calcium/calmodulin-dependent protein kinase II (CAMK2), to adipocyte function,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 73 publications
(85 reference statements)
0
22
0
Order By: Relevance
“…Our results showed that the continuously upregulated DEGs from D0 to Y2 (RC5 and RC2) enriched GP-BP and KEGG analysis were associated with immune response-related terms and pathways (such as lysosome and cytokine-cytokine receptor interaction), which might indicate the gain of immune functions after the loss of thermogenic capacity of BAT. The upregulated DEGs from D0 to Y2 were also enriched in the well-known adipogenesis-related KEGG pathways, such as the TGF-beta signaling pathway ( Yadav et al, 2011 ), MAPK signaling pathway ( Anderson, 2006 ), and calcium signaling pathway ( Dai et al, 2021 ), indicating these genes might be involved in the process of lipid accumulation during BAT whitening.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the continuously upregulated DEGs from D0 to Y2 (RC5 and RC2) enriched GP-BP and KEGG analysis were associated with immune response-related terms and pathways (such as lysosome and cytokine-cytokine receptor interaction), which might indicate the gain of immune functions after the loss of thermogenic capacity of BAT. The upregulated DEGs from D0 to Y2 were also enriched in the well-known adipogenesis-related KEGG pathways, such as the TGF-beta signaling pathway ( Yadav et al, 2011 ), MAPK signaling pathway ( Anderson, 2006 ), and calcium signaling pathway ( Dai et al, 2021 ), indicating these genes might be involved in the process of lipid accumulation during BAT whitening.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of this pathway in CNS is involved in neurite elongation and branching [62] as well as during cell cycle control [63]. It is also involved in the regulation of sympathetic tone [64] and long-term memory formation [65], and is implicated in anxiety and BD [66].…”
Section: Discussionmentioning
confidence: 99%
“…Hematoxylin and eosin (H and E) staining was performed in the liver tissue collected from Sam68 f/f and Sam68 LKO mice and fixed in 4% paraformaldehyde (PFA) by following the protocol reported by Dai et al [ 51 ]. For assessing Sam68 expression, liver tissues were collected from HFD- or ND-fed mice, and cryosections were subjected to immunofluorescence staining.…”
Section: Methodsmentioning
confidence: 99%